Central and Eastern European media in comparative perspective politics, economy and culture - Downey, John; Mihelj, Sabina (Ashgate Pub., 2012)
Examines the different economic, political, cultural, and transnational factors affecting developments in media systems across Central and Eastern Europe. This title argues that media systems are also cultural and economic institutions and there are other critical variables that might explain certain outcomes better.